2015
DOI: 10.1136/bmj.h4358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bivalent human papillomavirus vaccination on pregnancy outcomes: long term observational follow-up in the Costa Rica HPV Vaccine Trial

Abstract: ObjeCtiveTo examine the effect of the bivalent human papillomavirus (HPV) vaccine on miscarriage. DesignObservational long term follow-up of a randomized, double blinded trial combined with an independent unvaccinated population based cohort.setting Single center study in Costa Rica.PartiCiPants 7466 women in the trial and 2836 women in the unvaccinated cohort enrolled at the end of the randomized trial and in parallel with the observational trial component.interventiOn Women in the trial were assigned to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
(54 reference statements)
1
27
0
2
Order By: Relevance
“…The abstracts of the 45 remaining citations were read and 18 were excluded as not being relevant. Of the remaining 27 citations the full manuscript was examined and 5 [16][17][18][19][20] were chosen as relevant for the review (Table 1). Our aim was to provide an overview of the safety of HPV vaccination in pregnancy or immediately pre-conceptually.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abstracts of the 45 remaining citations were read and 18 were excluded as not being relevant. Of the remaining 27 citations the full manuscript was examined and 5 [16][17][18][19][20] were chosen as relevant for the review (Table 1). Our aim was to provide an overview of the safety of HPV vaccination in pregnancy or immediately pre-conceptually.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20] A total of 1,119 miscarriages occurred in the 8,092 pregnancies exposed to the HPV vaccine giving a miscarriage rate ranging from 6.6% 19 to 18.2%. 18 In 4 of the studies, [16][17][18]20 the exposed pregnancies were compared to either Hepatitis A vaccine (HAV) exposed [16][17][18] or placebo exposed pregnancies 20 and one study included both an HAV group and a placebo group. 17 None of the studies found a significantly increased rate of spontaneous abortion in the overall analyses.…”
Section: Spontaneous Miscarriagementioning
confidence: 99%
See 1 more Smart Citation
“…h4358) report on the long term follow-up for pregnancy outcomes in women enrolled in the Costa Rica HPV Vaccine Trial. 2 An earlier pooled analysis from this trial and the PApilloma TRIal against Cancer In young Adults (PATRICIA) trial found no overall association between vaccination using the bivalent vaccine and spontaneous abortion, but a small increase in risk in the subgroup of pregnancies conceived within 90 days of vaccination could not be completely ruled out. 3 In the Costa Rica trial, women were randomised to the bivalent HPV vaccine or control hepatitis A vaccine, with four years of follow-up, and crossover vaccination was offered before a four year post-intervention period.…”
mentioning
confidence: 83%
“…Der Impfschutz gegen Neuinfektionen mit HPV16 oder HPV18 ist höher als 90% in Frauen, die zum Zeitpunkt der Impfung keine HPV16/18 Infektion haben. Die HPV-Impfung wird in der Regel sehr gut toleriert und hat kaum Nebenwirkungen (14). Gegen bestehende Infektionen oder Krebsvorstufen konnte keine überzeugende Wirksamkeit der Impfstoffe gezeigt werden (15).…”
Section: Prävention Des Zervixkarzinomsunclassified